Assessment of Inflammatory Markers in Keelvayu Nivarana Churunam (KNC) Supplementation to Carrageenan-Induced Inflammatory Rats - Vijayabaskar, G.; Elango, V. (International Journal of Scientific Research in Biological Sciences, 2018)
The carrageenan-induced paw edema is a well-defined model of acute inflammation that a variety of inflammatory mediators involves in its development and has wildly been used to evaluate the anti-inflammatory effect of natural products. The results of the current study suggested that KNC possessed anti-inflammatory effects in carrageenan-induced rats. The anti-inflammatory mechanism of KNC may be related to the reduction of oxidative stress markers as MDA, GPx, Catalase and inflammatory markers PGE2, NO2, TNFα, IL6, IL-10, Myloperoxidase and IgM. Furthermore, the protective effect of KNC may result from anti-oxidative effects. Our findings provide new perspectives on the therapeutic use KNC in the management of inflammatory diseases including arthritis.